Designing positive psychology taking stock and moving forward - Sheldon, Kennon M. (Kennon Marshall); Kashdan, Todd.; Steger, Michael F. (New York ; Oxford : Oxford University Press, 2011)
Positive psychology exploded into public consciousness 10 years ago and has continued to capture attention around the world ever since. This book evaluates the first decade of this fledgling field of study from the perspective of nearly every leading researcher in the field.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Positive psychology; Psychology -- Methodology; Personality; Psychophysiology -- Methodology